Addition of Moringa Leaf Flour (Moringa oleifera L) in Rations on the Quality of Quail (Coturnix coturnix japonica) Eggs - Fenita, Yosi; Kaharuddin, Desia; Nurmeiliasari, Nurmeiliasari; Azis, Arif Rahman; Harlena, Yepi (Jurnal Sain Peternakan Indonesia, 2025)
This study aims to evaluate the use of moringa leaf flour (Moringa oleifera L) in rations on the quality of quail eggs. The researchers designed four treatments and five replications: P0, a ration without the use of Moringa leaf flour (control); P1, a ration containing 5% Moringa leaf flour; P2, a ration containing 10% Moringa leaf flour; and P3, a diet containing 15% Moringa leaf meal. These were analysed using ANOVA. The results showed that the use of Moringa leaf flour up to 15% had a significant effect (P<0.05) on yolk color but had no significant impact (P>0.05) on egg weight, yolk index, albumen index, haugh unit, shell weight, and thick shell. Based on the research results, incorporating Moringa leaf flour into rations up to 15% can enhance yolk colour without reducing egg weight, yolk index, albumen index, Haugh units, shell weight, and shell thickness.